2022
DOI: 10.3390/curroncol30010043
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Lymphocyte-to-Monocyte Ratio (LMR), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR) and Extramural Vascular Invasion (EMVI) in Locally Advanced Rectal Cancer

Abstract: Rectal cancer constitutes around one-third of all colorectal cancers. New markers are required to optimize the treatment. Extramural vascular invasion (EMVI) is a magnetic resonance imaging (MRI)-based negative prognostic marker. Lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR) or platelet-to-lymphocyte ratio (PLR) are blood-based systemic inflammatory response markers with proven prognostic value in many cancers, including CRC. We hypothesized whether there is a relationship between LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In other malignancies, the data on correlations between SIR markers and PD-L1 expression are conflicting [27,28]. We found no association between the SIR markers and the level of CEA, which corresponded to a retrospective study on rectal cancer patients [29]. The PD-L1 expression in the immune cells was positively correlated with both the inflammatory infiltrates and the tumor-infiltrating CD8 lymphocytes.…”
Section: Discussionsupporting
confidence: 64%
“…In other malignancies, the data on correlations between SIR markers and PD-L1 expression are conflicting [27,28]. We found no association between the SIR markers and the level of CEA, which corresponded to a retrospective study on rectal cancer patients [29]. The PD-L1 expression in the immune cells was positively correlated with both the inflammatory infiltrates and the tumor-infiltrating CD8 lymphocytes.…”
Section: Discussionsupporting
confidence: 64%
“…Comparisons with previous studies ( Prabawa et al, 2019 ; Gawiński, Hołdakowska & Wyrwicz, 2022 ; Ozmen et al, 2017 ) underscore the utility of PLR and NLR as non-invasive biomarkers for assessing disease severity, guiding treatment decisions, and predicting outcomes in cervical cancer. The establishment of these correlations further strengthens the potential clinical value of PLR and NLR in aiding risk stratification, treatment selection, and patient prognostication.…”
Section: Discussionmentioning
confidence: 76%
“…9,10 A growing number of studies have illustrated the diagnostic and prognostic values of inflammatory markers, such as LMR, NLR, systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI), in various cancers. [26][27][28][29] Recently, a study found that the Glasgow Prognostic Score (GPS), an inflammation-based prognostic evaluation system comprising measures of C-reactive protein and albumin, showed significant prognostic value in ENKTL. 30 However, the prognostic system is The results showed that the CONUT score was more efficient in predicting ENKTL prognosis than the IPI, KPI and PINK models.…”
Section: Discussionmentioning
confidence: 99%